AACRAO issues guidance on optional transcript notations. Issue 7 (September 2017) - Sutton, Halley
Abstract : Institutions of higher education have an obligation to inform other institutions of threats to their community from suspended and expelled students, according to a work group formed by the American Association of Collegiate Registrars and Admissions Officers. Based on the findings of this work group, AACRAO has released guidance to its members regarding the use of notations on transcripts for institutions that are either considering implementing notations or are required to do so under the laws of their state. The guidelines also outline ways that institutions could notify one another of potential community threats other than the academic transcript, including a student conduct transcript, a dean's certification letter, and a transcript insert.